Silymarin for the Prevention of Contrast-Induced Nephropathy: A Placebo-Controlled Clinical Trial - Sedighifard, Zohreh (Int J Prev Med, 2016)
BACKGROUND: Silymarin is a flavonoid complex with nephro-protective properties. We evaluated the efficacy of silymarin in the prevention of contrast-induced nephropathy (CIN). METHODS: This placebo-controlled clinical trial was conducted on 143 patients with chronic stable angina referring for elective coronary angiography. Patients with low to moderate risk for CIN were included and were randomized to receive silymarin (280 mg) or placebo 2 h before administration of the contrast material. A nonionic, iso-osmolar contrast material was used. Serum creatinine was measured before and 48 h after injection of the contrast material. CIN was defined as an increase in creatinine of ≥0.5 mg/dL or ≥25% from the baseline. RESULTS: Serum creatinine was increased by 0.02 ± 0.07 mg/dL (P = 0.004) with silymarin and by 0.04 ± 0.15 mg/dL (P = 0.008) with placebo after contrast material injection (between group difference = 0.01 ± 0.02 mg/dL, P = 0.881). CIN was occurred less frequently, though statistically nonsignificant, with silymarin compared with placebo (2.9% vs. 10.8%, Odds ratio [OR] [95% confidence interval (CI)] = 0.246 [0.050–1.203], P = 0.099). In the logistic regression analysis controlling for patients characteristics and baseline creatinine level, silymarin was nonsignificantly associated with lower frequency of CIN (OR [95% CI] = 0.203 [0.037–1.117], P = 0.067). CONCLUSIONS: We found a trend toward the efficacy of silymarin in preventing contrast-induced renal dysfunction. Further trials with larger sample size and in patients with higher risk of CIN are warranted.